A Theory-Based, Multidisciplinary Approach to Cocreate a Patient-Centric Digital Solution to Enhance Perioperative Health Outcomes among Colorectal Cancer Patients and Their Family Caregivers: Development and Evaluation Study - Wan, Su Wei (JMIR Publications Inc., 2022)
10.2196/31917